Estratégias de manejo sanitário nos núcleos de conservação in situ de bovinos curraleiro pé-duro e pantaneiro - Freitas, Thais Miranda Silva (2014)
Sanitary planning in cattle industry improves reproductive rates and increases economic profitability; however, the proposal of sanitary strategies depends on the prior knowledge about the herds and the factors that favors’ the occurrence of diseases. The aim of this study was to evaluate the occurrence, both individually and in the herd, of Brucella spp., Leptospira sp., Neospora caninum, bovine leucosis virus (BLV), bovine herpesvirus type 1 (BoHV-1), and bovine diarrhea virus (BVDV) in the Brazilian cattle breeds Curraleiro Pé-Duro (CPD) and Pantaneiro (PAN), as well as the associated risk factors. It also aimed at determining control strategies. We observed that brucellosis was under control in all herds, however we detected variable frequencies of serologically positive animals against Leptospira (CPD: 4,08% - 94,4% and PAN: 44,74% - 93,33 %), Neospora (CPD: 5,56% - 100% and PAN: 12,00% - 16,84 %), BLV (CPD:0,00% - 88,88% and PAN: 6,67% - 33,33 %), BoHV-1 (CPD: 39,24% - 95% and PAN: 0,00% - 59,00%) and BVDV (CPD: 6,67% - 78,5% and PAN: 4,08% - 78,57%). The most important risk factors associated to Curraleiro Pé-Duro infections were as follows: animals slaughter on the property, co-infections, free access to flooded areas and herd size. The major factors associated with seropositivity in Pantaneiro (PAN) herds were age above 24 months and artificial insemination, while veterinary assistance was a protection factor. The recommended measurements include prevention of positive animals introduction, vaccination, animal disposal, supply of colostrum from seronegative cows and sick animals segregation. This study assists professionals to evaluate the necessity of employing sanitary measurements.